Stakeholders’ Involvement in Brigada Eskwela of Bibiano A. Avenir Elementary School: An Evaluation - Condrillon, Loida (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the level of stakeholder involvement in Brigada Eskwela at Bibiano A. Avenir Elementary School to determine how stakeholder participation contributes to the sustainability and effectiveness of the program. Anchored on the principles of shared governance under Republic Act No. 9155 and the Filipino value of bayanihan, the study employed a descriptive-quantitative research design using a structured, researcher-made questionnaire validated by experts and pilot-tested for reliability. Purposive sampling was used to select teachers, learners, parents, and representatives from the Municipal Government Unit, Barangay Government Unit, Private Sector, and Local Civic Organizations who actively participated in Brigada Eskwela. Data were analyzed using frequency, percentage, weighted mean, and Analysis of Variance (ANOVA). The findings revealed that stakeholder involvement was generally high across volunteering, financial support, and services or donations, with participation ranging from Often Involved to Always Involved. Parents and the Barangay Government Unit consistently demonstrated the highest levels of involvement, while the Municipal Government Unit, Private Sector, and Local Civic Organizations also provided meaningful support. The analysis further revealed a statistically significant difference in the level of involvement among stakeholder groups, indicating that participation varied according to stakeholder type. The study concludes that sustained collaboration among stakeholders is essential for strengthening school readiness and the successful implementation of Brigada Eskwela. It recommends strengthening partnerships with the Municipal Government Unit and Private Sector, recognizing active stakeholders, establishing a resource mobilization framework, conducting regular stakeholder orientations, and creating a Brigada Eskwela monitoring committee to sustain stakeholder participation. This study supports Sustainable Development Goal (SDG) 4: Quality Education by promoting safe and supportive learning environments and SDG 17: Partnerships for the Goals by strengthening collaboration among schools and community stakeholders. The study contributes to educational and community sustainability by reinforcing shared governance, collaborative resource mobilization, and long-term school–community partnerships.